Clinopyroxene Dissolution Records Rapid Magma Ascent - Neave, David A.; Maclennan, John (Frontiers in Earth Science, 2020)
Magma ascent rates control volcanic eruption styles. However, the rates at which basaltic magmas ascend through the crust remain highly uncertain. Although recent studies have successfully exploited records of decompression driven degassing to estimate the rates at which H$_{\text{2}}$O-rich basalts ascend, such approaches cannot readily be applied to primitive and H$_{\text{2}}$O-poor basalts that erupt in ocean island and mid-ocean ridge settings. Here we present magma ascent rates obtained by modelling the dissolution of clinopyroxene crystals in a wehrlitic nodule from the primitive Borgarhraun lava flow in North Iceland. High-Al$_{\text{2}}$O$_{\text{3}}$ clinopyroxene core compositions are consistent with crystallisation near the Moho ($\sim$800 MPa), whereas low-Al$_{\text{2}}$O$_{\text{3}}$ clinopyroxene rims and inclusion compositions are consistent with crystallisation at or near the surface. We interpret low-Al$_{\text{2}}$O$_{\text{3}}$ rims and inclusions as the crystallised remnants of boundary layers formed by the dissolution of high-Al$_{\text{2}}$O$_{\text{3}}$ clinopyroxene during magma ascent. By combining characteristic rim dissolution lengths of 50--100 $\upmu$m with published experimental calibrations of clinopyroxene dissolution behaviour, we estimate that the Borgarhraun magma most likely decompressed and ascended at rates of 3.0--15 kPa.s$^{-\text{1}}$ and 0.11--0.53 m.s$^{-\text{1}}$ respectively. These rates are slightly faster than published estimates obtained by modelling the diffusive re-equilibration of olivine crystals, suggesting that the Borgarhraun magma either accelerated upwards or that it stalled briefly at depth prior to final ascent. Comparisons with other basaltic eruptions indicate that the H$_{\text{2}}$O-poor magma that fed the dominantly effusive Borgarhraun eruption ascended at a similar rate to some H$_{\text{2}}$O-rich magmas that have fed explosive eruptions in arc settings. Thus, magma ascent rates do not appear to correlate simply with magma H$_{\text{2}}$O contents. Overall, our findings confirm that primitive and H$_{\text{2}}$O-poor basalts can traverse the crust within days, and may erupt with little precursory warning of magma ascent.